Detectability of hepatocellular carcinoma by gadoxetate disodium‐enhanced hepatic MRI: Tumor‐by‐tumor analysis in explant livers. Issue 3 (10th October 2012) - Nakamura, Yuko; Tashiro, Hirotaka; Nambu, Junko; Ohdan, Hideki; Kakizawa, Hideaki; Date, Shuji; Awai, Kazuo
Abstract Purpose: To investigate the detectability of hepatocellular carcinoma (HCC) on Gd‐EOB‐enhanced MR images (Gd‐EOB‐MRI), we performed tumor‐by‐tumor analysis of pathologically confirmed tumors using explants from cirrhotic patients who had undergone liver transplantation. Materials and Methods: We studied 11 explanted livers and classified the tumor intensity during the arterial phase (AP) and the hepatobiliary phase (HBP) as low in HBP with early enhancement (EE) in AP (A), as high in HBP with EE in AP (B), as low in HBP without EE in AP (C), as high in HBP without EE in AP (D), and as iso‐intense in HBP with EE in AP (E). The diagnostic criteria for HCC were (i) pattern A and C, (ii) pattern A and E, (iii) pattern C and E, and (iv) patterns A, C, and E. Results: Of the 71 HCCs, 22 were not detected at MRI; of these, 9 were moderately differentiated and 13 were well‐differentiated HCCs. The sensitivity of Gd‐EOB‐MRI for diagnostic criteria 1, 2, 3, and 4 was 63.4%, 52.1%, 22.5%, and 69.0%. Conclusion: The maximum sensitivity of Gd‐EOB‐MRI for HCC was only 69.0% even when diagnostic criteria that included all previously reported HCC patterns were adopted. J. Magn. Reson. Imaging 2013;37:684—691. © 2012 Wiley Perioidicals, Inc.